Tertiary Lymphoid Tissue in the Tumor Microenvironment: From Its Occurrence to Immunotherapeutic Implications. (4th March 2015) - Di Caro, Giuseppe; Castino, Giovanni Francesco; Bergomas, Francesca; Cortese, Nina; Chiriva-Internati, Maurizio; Grizzi, Fabio; Mantovani, Alberto; Marchesi, Federica
Abstract : Recruitment of immune and inflammatory cells in the microenvironment of solid tumors is highly heterogeneous and follows patterns, varying according to the organ of origin and stage of disease, with critical roles in the process of cancer onset and progression. While adaptive cells are endowed with anti-tumor activities, inflammatory components of the immune infiltrate orchestrate an immunosuppressive microenvironment that reveals ambivalent functions of the immune contexture in the tumor milieu. The balance between opposing pro-tumoral and anti-tumoral immune pathways, which occur concomitantly in the tumor microenvironment, and the regulatory networks of these phenomena have been the target of several immunotherapeutic strategies. While the scarcity of adaptive immune effectors in tumors correlates with dismal prognosis, the pathways of activation of tumor-specific lymphocytes are yet to be fully elucidated. Recently, the occurrence of tertiary lymphoid tissue was revealed to be critical in mediating the dynamics of T cell recruitment and local activation of immune cells in the tumor microenvironment. Thus, tertiary lymphoid tissue assessment and targeting emerge as a promising approach for the design of novel prognostic immune signatures and immunotherapeutic strategies. The immunological behavior of tertiary lymphoid tissue, its occurrence in the tumor immune microenvironment and its clinical relevance are discussed here.